Alienation among University of Indonesia’s Psychology Students: A Comparative Study amongst First-Year, Second-Year, and Third-Year Students - Apriyanti, Harum Kusuma (Makara Human Behavior Studies in Asia, 2021)
Previous studies on alienation were mostly done within Western business context focusing on gender and racial/ ethnicity differences. However, their results were still equivocal. Less attention has been given to address the phenomenon in higher education context, especially in a developing country with collectivist culture. The present study examined gender differences at the levels of alienation amongst psychology students enrolling in semester two, four, six, and eight at the University of Indonesia. Participants were 107 female and 20 male university students (Mage = 19.95; range = 18– 24 years old). It was found that levels of alienation among male and female students were not significantly different. Although male students showed higher levels of alienation than their female counterparts, only semester six female and male students showed significance difference at their level of alienation. Results indicated that gender had a marginal influence on alienation. These findings suggested that the awareness of university demands and learning process are important; familiarity to learning environment is vital; and optimisation of the student support service is needed.